The Impact of Leadership Training on Student Learning Ability in Higher Education: Seen from the College Learning Effectiveness Inventory (CLEI) - Nurlaili, Eka Indah; Cahya, Septyan Budy; Fatoni, Fandi; Arif, Amirul; Susilowati, Fitriah Dwi; Wulandari, Ruri Nurul Aeni (International Journal of Emerging Research and Review, 2024)
Objective: This research refers to the purpose of student organizations that function as a means for students to develop intellectual abilities and skills, so student interest talent development activities as part of the educational process can be carried out through student organizations. This is important because honing skills through self-habituation and fulfilling the needs of life can form a balance between knowledge and skills as the basis of quality human resources in the development of the time. Method: It was carried out by analyzing the research model of the influence between student leadership training, including Pre-LKKMTD, LKKMTD, and LKKMTM on CLEI (measurement of higher education learning effectiveness inventory) in this measurement method. This procedure was used to test multiple regression research models. Results: It was stated that the participation of students in the leadership training of Pre-LKKMTD, LKKMTD, and LKKMTM students had a partial and simultaneous effect on student learning ability through the measurement of student learning ability effectiveness inventory (CLEI).  Novelty: in this study is to measure the impact of participation in the level of student leadership training on students' learning abilities by using a variety of six learning abilities, including self-efficacy, organization and attention to learning, stress control due to time and environmental pressures, involvement in college activities, emotional satisfaction, and communication in learning adapted from a research questionnaire called inventory higher learning effectiveness (CLEI).